Converting a Unicompartmental Knee Arthroplasty to a Total Knee Arthroplasty: Ensuring Primary Outcome - Pandit, H; Neely, J; Murray, D; Dodd, C (2011)
The reasons for failure of a medial unicompartmental knee arthroplasty include progression of arthritis in the retained lateral compartment, aseptic loosening, bearing dislocation, and infection. The overall incidence tends to be low. When planning revision surgery, one needs to be aware of certain pitfalls: (a) common radiological appearances (beware of physiological radiolucency); and (b) patients presenting with unexplained pain. The surgeon can ensure outcome equivalent to a primary total knee arthroplasty by careful preoperative planning and the correct surgical technique. © 2011 Elsevier Inc.